Penerapan Model Problem Based Learning (PBL) dalam Meningkatkan Kemampuan Berargumentasi Dalam Debat - Putri, Lulu; Asri, Aswati; Sulaiman, Miming Salmah (Fakultas Teknik Universitas Negeri Makassar, 2025)
This study aims to improve argumentation skills in debate among students of class XII IPA 5 SMA Negeri 10 Gowa through the application of Problem Based Learning (PBL) model. This study used a classroom action research design consisting of four main stages, namely planning, implementation, observation, and reflection. The research subjects were students of class XII IPA 5 SMA Negeri 10 Gowa consisting of 29 students. The data obtained from this study were analysed qualitatively and quantitatively. Based on the results of the study, the application of the Problem Based Learning (PBL) model succeeded in improving students' argumentation skills in debate. In cycle I, although there has been an increase in terms of student involvement and self-confidence, there are still weaknesses in terms of argument quality. Based on the results of the calculation, it can be seen that most students obtained a score range of 41-60 (sufficient), but only a few students obtained a score range of 81-100 (very good). However, in cycle II, after the application of strengthening argumentation techniques and additional exercises, students showed significant improvement in formulating arguments that were more logical, evidence-based, and responsive to opposing arguments. From this calculation, it can be seen that the largest increase occurred in the number of students who obtained a score of 81-100 which showed progress in clarity of argument, accuracy of data, and public speaking ability.